Degradation and recovery of graphene/polymer interfaces under cyclic mechanical loading. (8th September 2017) - Wang, Guorui; Gao, Enlai; Dai, Zhaohe; Liu, Luqi; Xu, Zhiping; Zhang, Zhong
Abstract: Interface failure is a common phenomenon for conventional composite materials when subjected to repeated mechanical loads, and it tends to be critical for nanocomposites due to several orders of magnitude enhancement in interfacial area. Herein, the graphene/poly(methyl methacrylate) (PMMA) interface when subjected to cyclic loading conditions exhibits obvious mechanical degradation through interfacial sliding, which has received little attention yet. Through a joint study of experimental tests and molecular dynamics simulations, the interface weakening is attributed to the formation of graphene buckles that not only reduces the interfacial contact area but also impairs the overall interfacial load transfer. However, reminiscent of the shape memory effect that is commonly triggered by temperature, conformational transition at the interfaces exhibits remarkable mechanical recovery under a moderate thermal stimulus, manifested by the interface reconstruction activated by van der Waals (vdW) forces. These findings elucidate the complex interactions between matrix and nanostructures in composite materials under cyclic loading conditions, and control over this mechanism could provide guidelines upon chemical design through tailoring the interfacial adhesion for specific applications.